Pengukuran Kinerja Organisasi dengan Penerapan Metode IPMS yang Terintegrasi dengan Metode SMART System (Studi Kasus : Fakultas “X”) - Petir Papilo (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Performance measurement is an important factor for any organization. Performance measurement is used as a basis for planning the organization to achieve the goals set in the future and as a tool for assessing the success of the organization. Performance measurement, today is no longer needed by business organizations wishing to internal organizational process improvement. Performance measurement at this point has penetrated to the non profit organization, one of which is an educational institution, in this case the university. This study aims to determine the level of achievement of the organization performance in education, especially within the scope of a faculty. By using this method has been established over 32 IPMS objective strategy to be achieved are summarized into 9 (nine) aspects are perspectives that exist on the SMART System Model. From the analysis of the priorities that have been made, there are five main factors that are the focus of attention and a critical indicator of success in achieving the vision and mission set by the Faculty “X”. The resoult that have been performed Faculty performance index values obtained were 3.72 level. Refers to a standard level of achievement that is, it can be concluded that the achievement of the Faculty “X”, is still far from the expected target.Key words : Performance, IPMS Methods, SMART System Model.